Socio-Economic Impact of Farmer Producer Company on its Members - Shelake, Chhakuli; Shelake, M. K. Rathod; Deore, Pradnyesh (Journal of Agricultural Extension Management, 2022)
The present study on the socio-economic impact of Farmer Producer Company on its members was undertaken in Nashik district of NorthWestern region of Maharashtra state with a sample size of 120 respondents from two Farmer Producer Companies. Mean and percentage change was calculated as pre and post participation of members in the FPOs. This percentage change was then considered for the extent of impact of each parameter. As regards the impact on social status, the changes observed were in the self-confidence of FPO members which was 40.87 per cent and 'Z' value (11.45), in interaction with officials it was 56.68 per cent and 'Z' value (9.11), in communication skills 56.25 per cent and 'Z' value (10.45) and the change in social participation was 53.59 per cent and 'Z' value (8.08). As regards the impact on economic status, changes observed were in employment generation which was 52.25 per cent and 'Z' value (9.58), in subsidiary occupation it was 43.12 per cent and 'Z' value (9.46), in annual income it was 61.27 per cent and 'Z' value (9.75), in annual expenditure 40.00 per cent and 'Z' value (7.24) and the change in annual savings was 81.56 per cent and 'Z' value (10.54). Overall the mean impact of Farmer Producer Company on its members after participation, over pre participation was 54.01 per cent.